ChemInform Abstract: The Ugi Four‐Component Reaction Enables Expedient Synthesis and Comparison of Photoaffinity Probes. Issue 9 (4th March 2014) - Bush, Jacob T.; Walport, Louise J.; McGouran, Joanna F.; Leung, Ivanhoe K. H.; Berridge, Georgina; van Berkel, Sander S.; Basak, Amit; Kessler, Benedikt M.; Schofield, Christopher J.
Abstract The four‐component Ugi reaction is applied to synthesize biotin and rhodamine tagged compounds (V) of which a series of photoaffinity probes (VIII) for 2‐OG oxygenase is derived.